Historiosophical analysis of the existential status of moral and ethical values as the basis of physical education - Poliakova, Oksana; Beaumont, E.; Poliakov, Igor (Національний технічний університет "Харківський політехнічний інститут", 2023)
The research devoted to the analysis of the value of human life and physical education as a means of overcoming existential threats.
Keywords: values; human existence; physical education; existential threats; цінності; людське існування; фізичне виховання; екзистенціальні загрози